If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -2 = 4(2x + -3) Reorder the terms: -2 + 10x = 4(2x + -3) Reorder the terms: -2 + 10x = 4(-3 + 2x) -2 + 10x = (-3 * 4 + 2x * 4) -2 + 10x = (-12 + 8x) Solving -2 + 10x = -12 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -2 + 10x + -8x = -12 + 8x + -8x Combine like terms: 10x + -8x = 2x -2 + 2x = -12 + 8x + -8x Combine like terms: 8x + -8x = 0 -2 + 2x = -12 + 0 -2 + 2x = -12 Add '2' to each side of the equation. -2 + 2 + 2x = -12 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = -12 + 2 2x = -12 + 2 Combine like terms: -12 + 2 = -10 2x = -10 Divide each side by '2'. x = -5 Simplifying x = -5
| 2n*n-5=3n*n^2*n*4 | | 4x^3+5x^2-18x+9=0 | | 3.5x+215=495 | | 30/y=6/1/5 | | 2(3x-7)-10=20 | | -4x-118=116+9x | | 21+x=-39 | | 2[7-5(1-x)]+6x=-12+3[6(x+1)-3x] | | -3.7t-4.1=6.3t+6 | | 21+x=-31 | | 3x+100=4x+x | | X+3=y-5 | | (x+7)+(2x-1)+(2x+3)=79 | | 3n+n+5=37 | | (12y+9x)-(x-y)= | | -3(5s-6)-18=-3(7s+2)-3 | | 3/4x2=21 | | 5X/6-3/8=7X/4 | | 16x-1024/x2 | | 4(n-25)=9n | | 18000+36000r+18000r^2=0 | | 100-207/8 | | 24.6176=3.14r^2 | | 4x-12=7+7x-4 | | 0.8=5.8/x | | 1.2x+5=3.4 | | 2x^3+3x^2-29x-60=0 | | (2/3)/(3/11) | | 18000+36000r+18000r^2=0 | | 4x=10x-36 | | 6(w-2)-4=-2(-8w+9)-2w | | x=15-4(3+32) |